Tanggung Jawab Notaris Sebagai Pemberi Kerja Dalam Hal Terjadi Perbuatan Melawan Hukum - Hoesin, Siti Hajati (Jurnal Hukum & Pembangunan, 2019)
Notaries need the help of others to carry out their duties and authorities in making authentic deeds. Other people who work help the Notary, do work in the Notary's office, as a worker. Workers become Notary employees or not become Notary employees, which is only limited to doing the work given by Notaries. In connection with the implementation of the position of a Notary Public there is a possibility that an unlawful act will occur by a person who does work at the Notary Office. When an act of unlawfulness occurs at the Notary's Office, the Notary will be held accountable, because the public who require the services of the Notary understands that for making an authentic deed is in the Notary's Office. In the event of an act against the law, the public does not distinguish whether the act against the law was committed by a Notary Public employee or not. What is certain is that unlawful acts occur in the Notary's office and are related to the implementation of the position of Notary in the context of making an authentic deed. Based on this, this paper tries to explain and analyze the responsibilities of a Notary in the event of an illegal act in the Notary's Office.